Media Relations Strategy of The Merdeka Belajar Kampus Merdeka (MBKM) Program 2023 in Building an Image in The Digital Era - Past Novel Larasaty; Lestari Nurhajati (ULTIMA Comm, 2024)
Government Public Relations or popularly referred to as GovPR in Indonesia, often considered by various parties, does not have a significant influence on various performance in government institutions. Even though various studies actually show the opposite, the success of the government in socializing programs and implementing policies, depends very much on the success of its public relations team in carrying out its functions. The purpose of this study is to learn what the public relations team of the 2023 MBKM (Merdeka Belajar Kelas Merdeka) Program under the Ministry of Education and Culture, Research and Technology is doing in an effort to build a positive image in the digital era. The PR team must work hard to increase the visibility of the MBKM program among the media, reach a wider target audience, and maximize the positive impact of the publicity. The function and performance of government PR related to media relations cannot be separated from the approach of media ecology theory. How the media and communication processes that occur affect perceptions, emotions, feelings and values that exist through the new technologies used. A real situation regarding the strengthening of digital communication used in our daily lives. This research uses qualitative methodology with a constructivist approach. Data collection was conducted by in-depth interviews and observation. This study aims to examine how the strategy of the MBKM 2023 program public relations team really is in building an image in the digital era.